DETERMINATION OF THE RATIONAL HEAT LOAD OF COOLING TOWERS OF HEAT DISCHARGE IN AIR CONDITIONING PROCESSES AT THE INLET OF ENERGY UNITS - Андрій Миколайович Радченко; Євген Іванович Трушляков; Сергій Анатолійович Кантор; Богдан Сергійович Портной (Авіаційно-космічна техніка та технологія, 2018)
The air conditioning processes (heat-humidity treatment) at the inlet of energy units by heat-energized refrigeration mechanisms with heat removal cooling towers of the cooling system are studied on the example of a gas turbine unit. Two-stage air cooling is considered applying a two-stage combined type heat-energized refrigeration mechanism, which applies the exhaust gas heat of a gas turbine unit and which includes absorption lithium-bromide and refrigerant ejector refrigeration mechanism as steps to convert waste heat into cold. Based on the results of modeling the operation of the cooling complex of a gas turbine unit, data was obtained on current heat loads on heat-energized refrigeration mechanisms and cooling towers in accordance with the climatic conditions of operation with different distribution of project heat loads on the air cooling stages and, accordingly, on the transformation of waste heat into cold. Due to the fact that the heat load on the cooling towers depends on the efficiency of transformation of waste heat into cold (heat coefficients) by absorption lithium-bromide and refrigerant ejector refrigeration mechanisms, a rational distribution of the project heat loads to the absorption and ejector stages of a combined type heat-energized refrigeration mechanisms that provides reduce heat load on cooling towers. It is demonstrated that due to this approach to determining the rational heat load on the cooling towers of the cooling system, which consists of calculation the redistribution of heat load between the  absorption lithium-bromide and refrigerant ejector cooling stages with different efficiency and transformation of waste heat (different heat coefficients) in accordance with current climate conditions, is possible to minimize the number of cooling with a corresponding reduction in capital expenditures on the air conditioning system at the inlet of gas turbine unit